A Carbamoyl Phosphate Synthetase II (CPSII) Deletion Mutant of Toxoplasma gondii Induces Partial Protective Immunity in Mice - Zhuo, Xunhui; Du, Kaige; Ding, Haojie; Lou, Di; Zheng, Bin; Lu, Shaohong (Frontiers in Microbiology, 2021)
Toxoplasma gondii is an obligate intracellular protozoan parasite. T. gondii primarily infection in pregnant women may result in fetal abortion, and infection in immunosuppressed population may result in toxoplasmosis. Carbamoyl phosphate synthetase II (CPSII) is a key enzyme in the de novo pyrimidine-biosynthesis pathway, and has a crucial role in parasite replication. We generated a mutant with complete deletion of CPSII via CRISPR/cas9 in type-1 RH strain of T. gondii. We tested the intracellular proliferation of this mutant and found it showed significantly reduced replication in vitro, though CPSII deletion did not completely stop the parasite growth. The immune responses induced by the infection of RHΔCPSII tachyzoites in mice was evaluated. During infection in mice, the RHΔCPSII mutant displayed notable defects in replication and virulence, and significantly enhanced the survival of mice compared with survival of RH-infected mice. We tracked parasite propagation from ascitic fluid in mice infected with the RHΔCPSII mutant, and few tachyzoites were observed at early infection. We also observed that the RHΔCPSII mutant induced greater accumulation of neutrophils. The mutant induced a higher level of T-helper type-1 cytokines (interferon-γ, interleukin-12). The mRNA levels of signal transducer and activator of transcription cellular transcription factor 1 and interferon regulatory factor 8 was significantly higher in the RHΔCPSII mutant-infected group. Together, these data suggest that CPSII is crucial for parasite growth, and that strains lack the de novo pyrimidine biosynthesis-pathway and salvage pathway may become a promising live attenuated vaccine to prevent infection with T. gondii.